Effects of aerobic or resistance exercise during neoadjuvant chemotherapy on tumor response and therapy completion in women with breast cancer: The randomized controlled BENEFIT trial - Martina E. Schmidt; Siri Goldschmidt; Charlotte Kreutz; Jana Müller; Andreas Schneeweiss; Anne M. May; Friederike Rosenberger; Joachim Wiskemann; Karen Steindorf (Journal of Sport and Health Science)
Background: The potential of exercise as a concurrent therapy for actively treated primary tumors has been suggested by emerging preclinical and observational studies. However, clinical trials regarding this question are scarce. Therefore, we conducted a randomized controlled trial investigating the effects of aerobic or resistance exercise concomitant to neoadjuvant chemotherapy (NACT) on tumor size. Methods: In the BENEFIT study (German title: Bewegung bei neoadjuvanter chemotherapie zur verbesserung der fitness), patients with breast cancer scheduled for NACT were randomly assigned to supervised resistance training (RT, n = 60) or aerobic training (AT, n = 60) twice weekly during NACT or to a waitlist control group (WCG, n = 60). The primary outcome, “change in tumor size”, as well as the secondary clinical outcomes pathologic complete response (pCR), type of surgery (breast conserving/mastectomy), axillary lymph node dissection (ALND, yes/no), premature discontinuation of chemotherapy (yes/no), and relative dose intensity (RDI) were derived from clinical records. Due to the highly skewed distribution, the primary outcome was categorized. Multiple (ordinal) logistic regression analyses were performed. Results: Overall, there was no significant difference in post-intervention tumor size between RT or AT and WCG. However, there was a significant effect modification by hormone receptor (HR) status (pinteraction = 0.030). Among patients with HR+ tumors, results suggest a beneficial effect of AT on tumor shrinkage (odds ratio (OR) = 2.37, 95% confidence interval (95%CI): 0.97‒5.78), on pCR (OR = 3.21, 95%CI: 0.97‒10.61); and on ALND (OR = 3.76, 95%CI: 0.78‒18.06) compared to WCG. The effects of RT were slightly less pronounced. For HR−subtypes, beneficial effects on RDI were found for AT (OR = 3.71, 95%CI: 1.20‒11.50) and similarly for RT (OR = 2.58, 95%CI: 0.88‒7.59). Both AT and RT had favorable effects on premature discontinuation of chemotherapy (OR (no vs. yes) = 2.34, 95%CI: 1.10‒5.06), irrespective of tumor receptor status. Conclusion: While there was no significant effect on the primary outcome in the overall group, aerobic and resistance exercise concomitant to NACT seem to beneficially affect tumor shrinkage and pCR, reduce the need for ALND among patients with HR+ breast cancers, and prevent low RDI among patients with HR– breast cancers. These results warrant confirmation in further trials.